Transnational civil society in Asia the potential of grassroots regionalization - Avenell, Simon Andrew; Ogawa, Akihiro 1968- (Routledge, Taylor & Francis Group, 2022)
"This edited volume addresses how transnational interactions among civil society actors in Asia and its sub-regions are helping to strengthen common democratic values and transform dominant processes of policymaking and corporate capitalism in the region. The contributors conceive of transnational civil society networks as constructive vehicles for both informing and persuading governments and businesses to adopt, modify, or abandon certain policies or positions. This volume investigates the role of such networks through a range of interdisciplinary approaches, bringing together case studies on Asian transnationalism from South, Southeast, and Northeast Asia across four key themes: local transformations and connections, diaspora politics, cross-regional initiatives and networks, and global actors and influences. Chapters demonstrate how transnational civil society is connecting people in local communities across Asia, in parallel to ongoing tensions between nation-states and civil society. By highlighting the grassroots regionalization emerging from ever-intensifying information exchange between civil society actors across borders - as well as concrete transnational initiatives uniting actors across Asia - the volume advances the intellectual mandate of redefining 'Asia' as a dynamic and interconnected formation. Transnational Civil Society in Asia will appeal to students and scholars of international relations, politics and Asian studies more broadly."
Keywords: Zivilgesellschaft; Transnationale Politik; Asien; Civil society / Asia / Case studies; Democracy / Asia / Case studies; Asian cooperation; Transnationalism; Transnationalisme; Civil society; Democracy; Asia; Case studies; Aufsatzsammlung